2018
DOI: 10.1097/sap.0000000000001314
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Vasopressor-Induced Symmetrical Peripheral Gangrene

Abstract: BackgroundSymmetrical peripheral gangrene (SPG) is an uncommon syndrome showing symmetrical gangrene in acral regions without evidence of large-vessel occlusion or vasculitis. Intravenous vasopressors are frequently used to manage hemodynamically unstable patients. There have been few reports about SPG after using inotropics. However, risk factors for SPG have not been extensively studied. Therefore, the objective of this study was to analyze several cases of SPG and identify risk factors for SPG.MethodsFrom O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…This study found a significant difference in the use of inotropic agents, similar to the findings of domestic and international studies on limb necrosis due to vasoconstrictive agents and inotropic agents [23,24]. Blood pressure was measured on the third day after birth, after 72 hours when the PDA was closed; it was found that the blood pressure of premature newborns with peripheral arterial ischemia was significantly more likely to be in the 50th percentile or lower.…”
Section: Discussionsupporting
confidence: 82%
“…This study found a significant difference in the use of inotropic agents, similar to the findings of domestic and international studies on limb necrosis due to vasoconstrictive agents and inotropic agents [23,24]. Blood pressure was measured on the third day after birth, after 72 hours when the PDA was closed; it was found that the blood pressure of premature newborns with peripheral arterial ischemia was significantly more likely to be in the 50th percentile or lower.…”
Section: Discussionsupporting
confidence: 82%
“…The use of vasopressors compounds the risk of ischemia in patients with disseminated intravascular coagulation by inducing vasoconstriction in the setting of underlying hematologic dysregulation. 3 , 5 BT may alleviate the local effect of vasopressors to improve tissue oxygenation. A prospective trial was initiated in 2011 to study the use of BT in vasopressor-induced digital ischemia, although it was terminated due to low accrual.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with sepsis treated with epinephrine and dopamine in our study may have been refractory to norepinephrine, suggesting that they had a more severe status. Moreover, results of a multivariable model used in a recent retrospective cohort study reported that only dopamine among all the vasopressors, was associated with PG development in ICU patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%